Bringing together scattered and localized actors: political consumerism as a tool for self‐organizing anti‐mafia communities. (September 2015) - Forno, Francesca; Wahlen, Stefan; Laamanen, Mikko
Abstract By introducing political consumerism into the vocabulary of the anti‐Mafia movement, Addiopizzo activists – a group of post‐grad students formed in 2004 – have been able to effectively encourage a growing number of entrepreneurs and shopkeepers to join together to oppose the extortion racket systems in the city of Palermo, Italy. By referring to social movements approaches, the paper discusses how a small, locally‐based Social Movement Organization (SMO) has succeeded in mobilizing different segments of society by connecting its symbolic, material and structural dimensions. Data for the analysis came from several sources: interviews with the activists themselves, participant observation, media analysis and a structured questionnaire distributed to 277 entrepreneurs who had joined the mobilization.